ANALISIS PENGARUH ENVIRONMENTAL CONCERN TERHADAP GREEN PURCHASE INTENTION DENGAN GREEN PRODUCT INVOLVEMENT DAN SELF-IMAGE CONGRUENCE SEBAGAI VARIABEL MEDIASI (Studi Pada Produk Hijau Merek Herborist) - Kusuma Siregar, Rizqy Dwi; Ferdinand, Augusty Tae (Diponegoro Journal of Management, 2023)
ABSTRACT Green marketing is a further action strategy from sustainability to repair an increasingly damaged environment. Aside from being a human responsibility, green marketing trends are also used to gain a competitive advantage amid the increasingly fierce competition in the cosmetics industry. Herborist is one of the products that carry out green marketing. Although Herborist is a product that is well known by many people, its marketing has not been maximized so it can be said that it is still less competitive than other green products. On the other hand, consumers are increasingly aware that environmental damage cannot be ignored so green consumption is increasing. This concern for the environment is used by Herborist products to attract market attention. In addition to this phenomenon, a gap in the results of previous studies was found, namely the inconsistent relationship between Environmental Concern and Green Purchase Intention. This study aims to develop a conceptual model on how to manage Environmental Concern by using the Self-Congruence Theory approach so as to increase Green Purchase Intention in Herborist beauty products through Green Product Involvement and Self-Image Congruence. Data collection was obtained by 110 respondents using the questionnaire method with the criteria of having purchased Herborist products at least once and domiciled in Semarang. The data processed and analyzed using the Structural Equation Modeling (SEM) method, using the Analysis Moment of Structural (AMOS) software. The results of this study found that environmental concern has a positive and significant impact on green purchase intention through green product involvement and self-image congruence. Therefore, all hypotheses in this study were accepted. The managerial implications of this research are expected can be useful in developing the company's marketing strategy for Herborist products